Hierarchical Materials: Probing Zinc–Protein–Chelant Interactions Using Gold Nanoparticles Functionalized with Zinc‐Responsive Polypeptides (Part. Part. Syst. Charact. 11/2014). (November 2014) - Mak, Wing Cheung; Selegård, Robert; Garbrecht, Magnus; Aili, Daniel
<x xml:space="preserve">Abstract</x> On page 1127, N. Pazos‐Perez and colleagues use anodized aluminum oxide with parallel linear periodicities as a template to organize gold nanorods. The long axes of the gold nanorods are oriented along the lines, inducing tip‐to‐tip plasmonic coupling and generating highly active hotspots. Additionally, the inherent hydrophobicity of the substrate allows for analyte concentration determination, making these substrates ideal surface‐enhanced Raman scattering platforms. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>